Creating Innovation Based on Superior Business Capabilities and Entrepreneurial Networks to Enhance Marketing Performance - ., Murwatiningsih; Oktarina, Nina (KnE Social Sciences, 2020)
This research empirically tests and analyzes the creation of innovation through superior business capabilities and entrepreneurial networks to enhance the marketing performance of micro, small and medium-sized confection enterprises in Semarang City. This research takes 100 respondents as its samples using an incidental sampling technique. The respondents are owners/management of confection businesses. The data are collected using questionnaire and analyzed by employing descriptive technique and Structural Equation Model (SEM) with AMOS version 18 software. The research results generally conclude that superior business capabilities influence innovation, entrepreneurial networks, and marketing performance. Entrepreneurial networks influence innovation and marketing performance, and innovation influences the marketing performance of micro, small and medium-sized confection enterprises in Semarang City. Keywords: innovation, superior business capabilities, entrepreneurial networks, marketing performance.